PENGARUH PROMOTION MIX DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN DI PLATFORM E-COMMERCE SHOPEE DI KOTA BATURAJA - Dodi, Dodi; Munajat, Munajat; Fifian Permata Sari (LPSDI Bina Patria, 2025)
This study aims to analyze the influence of Promotion Mix and lifestyle on purchasing decisions on the Shopee e-commerce platform, focusing on fashion category customers (clothing and shoes) in Baturaja. Promotion Mix, which includes direct selling, advertising, public relations, and sales promotions, is an important element in attracting consumer attention and increasing sales volume. Meanwhile, lifestyle reflects an individual's lifestyle patterns in activities, interests, and opinions, which contribute to purchasing decision making. The research method used is quantitative, with path analysis to measure the direct and indirect effects between the research variables. Data were collected through questionnaires distributed to 180 respondents. The results of the analysis show that the Promotion Mix variable has a direct and significant effect on purchasing decisions, while lifestyle functions as an intervening variable that strengthens the relationship between Promotion Mix and purchasing decisions. Path analysis also reveals that the combined influence of these two variables contributes significantly to Shopee customers' purchasing decisions. Effective marketing strategies and an understanding of consumer lifestyles greatly influence purchasing decisions. These findings are expected to be a strategic basis for Shopee in designing more effective and innovative promotional campaigns, as well as contributing to digital marketing literature